Erratum: Correction to: Developing a tablet computer-based application ('App') to measure self-reported alcohol consumption in Indigenous Australians - Lee, K.; Wilson, S.; Perry, J.; Room, R.; Callinan, S.; Assan, R.; Hayman, N.; Chikritzhs, Tanya; Gray, Dennis; Wilkes, Edward; Jack, P.; Conigrave, K. (Biomed Central Ltd, 2018)
After publication of the original article [1] it was noted that the name of author, Peter Jack, was erroneously typeset in both the PDF and online formats of the manuscript as Peter Jack GradDipIndigH. This inclusion of his qualification as part of his surname was introduced during typesetting, thus the publisher apologises for this error. The original article has also been updated to reflect this correction.